Synthesis of Polystyrene Microspheres to be Used as Template in the Preparation of Hollow Spherical Materials: Study of the Operative Variables - Gorsd, Marina Noelia (2012)
Mono-disperse polystyrene (PS) spheres were synthesized. The styrene polymerization was carried out using 4,4´-azobis 4-cyanovaleric acid (ACVA) or potassium persulfate (KPS) as initiators in the presence of polyvinyl pyrrolidone (PVP) as surfactant or stabilizing agent. Size measurement and its distribution were followed by scanning electron microscopy. A very narrow size distribution was obtained by controlling the synthesis temperature. For both initiators, it was observed that smaller PS particles are obtained when PVP amount increases. Besides, the ssphere size decreased when KPS amount increased at a fixed PVP concentration. Similar results were obtained for the polystyrene spheres synthesized using ACVA as initiator. On the other hand, the influence of a co-monomer addition in the sphere size was also analyzed. The suitable selection of the initiator type and its concentration, as well as the surfactant agent amount, led to a controlled obtainment of the polystyrene microspheres, appropriate to be used as template in the synthesis of hollow spherical materials.